2009
DOI: 10.1038/sj.bjc.6605007
|View full text |Cite
|
Sign up to set email alerts
|

De novo fatty-acid synthesis and related pathways as molecular targets for cancer therapy

Abstract: Enhanced lipid biosynthesis is a characteristic feature of cancer. Deregulated lipogenesis plays an important role in tumour cell survival. These observations suggest that enzymes in the lipid synthesis pathway would be rational therapeutic targets for cancer. To this end, we review the enzymes in de novo fatty-acid synthesis and related pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
346
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 454 publications
(372 citation statements)
references
References 33 publications
14
346
1
11
Order By: Relevance
“…Since phospholipid biosynthesis, but not glycerol phosphate shuttling, occurs in the endoplasmic reticulum, we can assume that SLC37A1 protein could have a role in the transport of G3P into endoplasmic reticulum to provide phospholipid biosynthesis. Fatty acid synthase (FAS), the main enzyme involved in de novo fatty acid synthesis, is coordinately regulated at the transcriptional level together with other lipogenic genes to provide balanced amounts of lipids for membrane biosynthesis [7,13]. FAS concentration is very low in non-cancerous cells, while it is overexpressed in a wide variety of human cancer cells, supporting the synthesis of phospholipids required for the newly synthesized cellular membrane [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since phospholipid biosynthesis, but not glycerol phosphate shuttling, occurs in the endoplasmic reticulum, we can assume that SLC37A1 protein could have a role in the transport of G3P into endoplasmic reticulum to provide phospholipid biosynthesis. Fatty acid synthase (FAS), the main enzyme involved in de novo fatty acid synthesis, is coordinately regulated at the transcriptional level together with other lipogenic genes to provide balanced amounts of lipids for membrane biosynthesis [7,13]. FAS concentration is very low in non-cancerous cells, while it is overexpressed in a wide variety of human cancer cells, supporting the synthesis of phospholipids required for the newly synthesized cellular membrane [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to FAS, several other enzymes involved in lipid metabolism have recently been shown to be implicated in tumor growth and viability [13]. In mammals, two ACS isozymes, ACSL4 and ACSL5, GPAT enzymes, and the LPAAT-b isoform are all overexpressed by a number of human cancers cells, including glioma, lung, breast, and colon carcinoma [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focused on the investigation of positive feedback loop. FASN is a complex multifunctional enzyme that plays a central role in endogenous lipogenesis in mammals [28,29] . It has been reported that the overexpression of FASN together with a high proliferative index of breast cancer cells are associated with a nine-fold increased risk of patient mortality [30] .…”
Section: Discussionmentioning
confidence: 99%